Autophagy Determines Distinct Cell Fates in Human Amnion and Chorion Cells - Severino, Mary Elise L; Richardson, Lauren; Kammala, Ananth Kumar; Radnaa, Enkhtuya; Khanipov, Kamil; Dalmacio, Leslie Michelle M; Mysorekar, Indira U; Kacerovsky, Marian; Menon, Ramkumar (Autophagy reports, 2024)
Human fetal membranes (amniochorion) that line the intrauterine cavity consist of two distinct cell layers; single-layer amnion epithelial cells (AEC) and multilayer chorion trophoblast cells (CTC). These layers are connected through a collagen-rich extracellular matrix. Cellular remodeling helps support membrane growth and integrity during gestation and helps to maintain pregnancy. Preterm prelabor rupture of the human amniochorionic (fetal) membrane (pPROM) is antecedent to 40% of all spontaneous preterm birth. Oxidative stress (OS) induced activation of the p38 MAPK due to various maternal risk exposures and the amniochorion cells' senescence are reported pathological features of pPROM. Our transcriptomics analysis implicated dysregulated autophagy and epithelial-mesenchymal transition (EMT) in fetal membranes from pPROM. The molecular interplay between OS-induced p38 MAPK activation, autophagy, and EMT was investigated in AECs and CTCs to better understand the involvement of autophagy and EMT. We report the differential impact of OS on the autophagic machinery in AECs and CTCs, resulting in distinct cell fates. In AECs, OS-induced p38 MAPK activation causes autophagosome accumulation and reduced autophagic flux mediated by decreased ULK1 activity and kinase activity, leading to senescence. In CTCs, induction of autophagy has a limited effect; however, inhibition of autophagy led to SQSTM1-mediated EMT of trophoblast cells. Autophagy, EMT, and senescence were associated with proinflammatory changes. Thus, AECs and CTCs respond differently to OS via differential autophagy response, partly mediated via p38 MAPK. Besides senescence, OS-induced autophagy dysregulation in amniochorion cells may play a mechanistic role in pPROM pathophysiology.
Keywords: autophagy; p38 MAPK; epithelial-mesenchymal transition; amnion; senescence; chorion; preterm birth; Membrane rupture; trophoblast; preterm premature rupture of membranes; Oxidative stress